Analisis angka kuman pada makanan siap saji - Chandra, Fifia; Ernalia, Yanti (Universitas Jenderal Achmad Yani Yogyakarta, 2021)
Background: Food poisonings in Indonesia mostly occurred in catering services. Salmonella sp., Campylobacter, Listeria, and E. coli are the types of bacteria that frequently cause food poisoning. Objective: The study aimed to detect Salmonella sp. on foods served in several restaurants. Methods: This research is a survey research with crossectional method. Selection of the restaurant was done by random sampling. There were 12 subdistricts and two restaurants were selected from each subdistrict in Pekanbaru, Riau, Indonesia. There were two types of foods consisted of animal and beans or vegetables, then 48 types of food from 24 Restaurants were obtained. The identification step was proceeded in Biochemical Laboratory of Health Polytechnic of Ministry of Health of Riau Province. This method was SNI 01-2332.2-1006 which was done with several steps of testing, namely pre-enrichment, enrichment, isolation and identification, and biochemical test. Data was presented in narration and univariate analysis for the frequency distribution of data. Results: In isolation and identification test steps on SS agar, there were 17 colonies found and suspected as Salmonella sp.. According to this data, it was found that 17 out of 48 (35,41%) of food samples in the restaurant contained bacteria. However, in the final steps of biochemical test there were 6 out of 48 total (12,5%) food samples contained Salmonella sp, and was found in 6 out of 24 restaurant (25%) and in 6 of 12 (50%) subdistricts. Foods that contained Salmonella sp. were rendang, chicken seasoning, tuna fish, vegetarian bak, fried shrimp, and grilled chicken Conclusion: Salmonella sp. found on foods served in several restaurants.